The Effectiveness of Project Based Learning in Improving Students’ Mathematics Problem Solving Ability - Murtiyasa, Budi; Budiningsih, Budiningsih (Jurnal Pendidikan Progresif, 2022)
The Effectiveness of Project Based Learning Model on Students' Mathematics Problem Solving Ability. Objectives:The aim of this  research was to describe mathematics learning with the Project Based Learning model on mathematical problemsolving abilitties in class X SMA N 1 Simo. Methods: This type of research was quantitative research. The study took two classes as research subjects consisting of thirty-six students in each class. Data collection techniques were carried out with test instruments and documentation. The design of this research was quasi-experimental by comparing test results from different subjects. The Sampling technique in this research is a simple random sampling technique, which is a sampling technique by taking sample members from the population at random without regard to the existing strata in the population. Data analysis techniques esed include Analysis of Variance Test and Multiple Comparison Test.Findings: The mean of the experimental class and control class, namely the experimental class with the PjBL learning model, is 84.72 while the control class with the conventional learning model is 65.53. Conclusions:The result of this research indicate that class X MIPA 5 which is treated with project based learning model has better problem solving ability than class X MIPA 4 which is treated with conventional learning model. Keywords: project based learning model, mathematical problem solving abilityDOI: http://dx.doi.org/10.23960/jpp.v12.i2.202225